Answer:
![a_n= (n+2)^2-1 =(n+3)(n+1)](https://img.qammunity.org/2022/formulas/mathematics/high-school/n82p7gbvmti7otxfi7gpy4awk9k2zqghoh.png)
Explanation:
If you add 1 to each number, you get a perfect square: 4, 9, 16, 25, 36, which are the squares of 2, 3, 4, 5, 6...
![a_n= (n+2)^2-1 =(n+3)(n+1)](https://img.qammunity.org/2022/formulas/mathematics/high-school/n82p7gbvmti7otxfi7gpy4awk9k2zqghoh.png)
Note that the two expressions are the same, but one might be more convenient than the other if you are manually calculating terms.